2022
DOI: 10.1186/s40959-022-00137-y
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in cancer patients who develop stroke

Abstract: Background Acute ischemic stroke (Stroke) and transient ischemic attacks (TIA) are known complications in cancer patients and those with atrial fibrillation (AF). The role AF plays in Stroke/TIA in the setting of cancer is unclear. The purpose of this study was to assess the relationship between AF and Stroke/TIA in cancer patients. Methods We conducted a case-control study comparing all patients who developed Stroke/TIA from 2014 to 2019 following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another important clinical consideration is atrial fibrillation (AF) in cancer patients who develop stroke [10]. About 2-5% of cancer patients have AF at the time of diagnosis, making it yet another common condition in this population [17][18][19]. A case-controlled study of cancer patients who experience stroke/transient ischaemic attack (TIA) with matched cancer patients without stroke/TIA found that AF, prior ischaemic stroke, ongoing cancer therapy, dyslipidaemia, and renal disease are independent risk factors for stroke/TIA [19].…”
Section: Therapeutic or Preventive Management Of Stroke In Cancer Pat...mentioning
confidence: 99%
See 3 more Smart Citations
“…Another important clinical consideration is atrial fibrillation (AF) in cancer patients who develop stroke [10]. About 2-5% of cancer patients have AF at the time of diagnosis, making it yet another common condition in this population [17][18][19]. A case-controlled study of cancer patients who experience stroke/transient ischaemic attack (TIA) with matched cancer patients without stroke/TIA found that AF, prior ischaemic stroke, ongoing cancer therapy, dyslipidaemia, and renal disease are independent risk factors for stroke/TIA [19].…”
Section: Therapeutic or Preventive Management Of Stroke In Cancer Pat...mentioning
confidence: 99%
“…About 2-5% of cancer patients have AF at the time of diagnosis, making it yet another common condition in this population [17][18][19]. A case-controlled study of cancer patients who experience stroke/transient ischaemic attack (TIA) with matched cancer patients without stroke/TIA found that AF, prior ischaemic stroke, ongoing cancer therapy, dyslipidaemia, and renal disease are independent risk factors for stroke/TIA [19]. The study also indicated that a higher CHA 2 DS 2 -VASc score significantly potentiates the risk in people with active cancer independent of AF [19].…”
Section: Therapeutic or Preventive Management Of Stroke In Cancer Pat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Lipshultz, et al [6] found that survivors of childhood cancer, regardless of exposure to cardiotoxic treatments, had cardiovascular abnormalities related not only to abnormal left ventricular structure and function but also to increased traditional risk factors for atherosclerotic disease and systemic in lammation. Most recently, the relationship between atrial ibrillation (AF) and Stroke/ transient ischemic attacks (TIA) in cancer patients was conducted in a case-control study, the CHA 2 DS 2 -VASc score, which components such as heart failure, hypertension, old age, and diabetes mellitus were found to be associated with stroke in the general population, signi icantly increases the risk of stroke in cancer patients regardless of the presence of AF [7].…”
Section: Open Accessmentioning
confidence: 99%